Kecemasan Penderita Gagal Ginjal Kronik yang Menjalani Hemodialisis - Tofik Hidayat (Jurnal Keperawatan Notokusumo, 2014)
Background : Chronic Renal Failure (CRF) is a chronic decline in renal function is generally not reversible and quite advanced. Chronic renal failure with hemodialysis therapy (HD) in Indonesia and generally in developing countries is not just a matter of medical aspects alone, but involves psychological aspects and social aspects. Significant psychological problems found in CRF patients undergoing HD therapy is depression, dementia, drug use and alkhohol, anxiety and personality disorders. Research on the number of patients with renal failure who are undergoing this treatment permanent shows that most of them experience anxiety, feelings of despair, lose hope and depression are quite heavy. Objective : The aim of this study was to know about Anxiety Chronic Renal Failure Patients Undergoing Hemodialysis is. Method: The study of quantitative non-experimental. The research design used was a descriptive cross sectional analytic approach. Result: the results showed that anxiety CRF patients undergoing HD in HD Unit Hospital Dr. Soeradji Tirtonegoro Klaten is anxiety were 12 persons (34.23%) and 11 severe anxiety (31.4%). in detail there are changes and differences in anxiety levels in CRF patients undergoing HD by age, gender, socioeconomic status (monthly income), duration of therapy and frequency therapy HD. Conclusion: Anxiety CRF patients undergoing HD in HD Unit Hospital Dr. Soeradji Tirtonegoro Klaten is anxiety were 12 persons (34.23%) and 11 severe anxiety (31.4%).